Non-invasive Central and Peripheral Stimulation: New Hope for Essential Tremor? - Chalah, Moussa A.; Lefaucheur, Jean-Pascal; Ayache, Samar S. (Frontiers in Neuroscience, 2015)
Essential tremor (ET) is among the most frequent movement disorders. It usually manifests as a postural and kinematic tremor of the arms, but may also involve the head, voice, lower limbs and trunk. An oscillatory network has been proposed as a neural correlate of ET, and is mainly composed of the olivocerebellar system, thalamus and motor cortex. Since pharmacological agents have limited benefits, surgical interventions like deep brain stimulation are the last-line treatment options for the most severe cases. Non-invasive brain stimulation techniques, particularly transcranial magnetic or direct current stimulation, are being used to ameliorate ET. Their non-invasiveness, along with their side effects profile, makes them an appealing treatment option. In addition, peripheral stimulation has been applied in the same perspective. Hence, the aim of our review is to shed light on the emergent use of noninvasive central and peripheral stimulation techniques in this interesting context.